Preparation method and application of amorphous Fenton-like catalyst Fe-Ni-coated CACD

The Fe-Ni@CACD catalyst is prepared by combining citric acid-modified β-cyclodextrin with iron-nickel bimetallic, which solves the problem of low efficiency of H2O2 degradation perfluoro compounds in the prior art, and achieves an efficient and reusable catalytic degradation effect.

CN119819366APending Publication Date: 2025-04-15GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411873723.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, in catalyzing the degradation of perfluoro compounds by H2O2, there are problems such as iron sludge precipitation, low catalytic efficiency and low H2O2 utilization efficiency in catalyzing the degradation of perfluoro compounds by H2O2, and it is difficult to effectively remove perfluoro compounds in water.

Method used

By combining citric acid-modified β-cyclodextrin with iron-nickel bimetallic catalytic activity center, Fe-Ni@CACD catalyst was prepared to catalyze H2O2 degradation of PFBA.

Benefits of technology

This catalyst exhibits good degradation performance in the Fenton-like system, overcomes the disadvantages of the traditional Fenton oxidation process, improves the catalytic performance and H2O2 utilization efficiency, and can be reused multiple times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819366A_ABST
    Figure CN119819366A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an amorphous Fenton-like catalyst Fe-Ni-coated CACD, namely beta-cyclodextrin (beta-CD) is used as a substrate, and the beta-CD which is originally hydrophilic is changed into a hydrophobic material through esterification crosslinking modification of anhydrous citric acid. The Fe-Ni-coated CACD has the advantages that the Fe-Ni-coated CACD is used as a carrier, the Fe-Ni-coated CACD is fixed on the surface of a cyclodextrin base and an internal cavity through metal coordination and complexation, the amorphous Fenton catalytic material Fe-Ni-coated CACD is formed, and the Fe-Ni-coated CACD shows efficient and stable catalytic performance in the process of degrading PFBA by activating H2O2 to generate. OH. Under the conditions that the temperature is 35 DEG C, the pH value is 3, the adding amount of the Fe-Ni-coated CACD catalyst is 1.50 g / L, the adding amount of H2O2 is 40.00 mM and the rotating speed of a stirrer is 450 r / min, the degradation rate of the Fe-Ni-coated CACD Fenton-like system on 0.10 mg / L of perfluorobutyric acid (PFBA) within 30 min is 89.46%, good degradation efficiency is shown, huge potential is shown in the aspect of perfluorinated compound wastewater treatment, and a certain basis is provided for treatment of perfluorinated compounds in a water environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization and water treatment, and specifically relates to a method for preparing a Fenton-like catalytic material of a beta-cyclodextrin-based complex metal iron-nickel, and is used for catalyzing H2O2 to degrade perfluorinated compounds in water. Background Art

[0002] Perfluorinated compounds (PFCs) refer to a new type of organic compound in which all hydrogen atoms connected to carbon atoms in the compound molecule are replaced by fluorine atoms. Among them, those with more than 8 carbon atoms in the carbon chain (C8-C14) are called long-chain PFCs, and those with less than 8 carbon atoms (C4-C7) are called short-chain PFCs. PFCs are widely used in food packaging, non-stick pan coatings, lubricant production, textiles, pharmaceuticals and other fields. They are a new type of persistent organic pollutants (POPs) that are difficult to degrade naturally. Related toxicology has confirmed that PFCs have liver toxicity, immunotoxicity, neurotoxicity, reproductive toxicity, etc. Therefore, the prevention and control of PFCs pollution in water environment has become a research hotspot. Among many removal methods, heterogeneous Fenton oxidation method has the advantages of high efficiency, high H2O2 utilization rate, wide pH application range, etc. for organic matter degradation. It can also overcome the disadvantages of traditional Fenton technology in producing iron sludge and avoid secondary pollution, which has good research and development value. Metallic iron is a commonly used H2O2 activator. It can generate highly oxidizing ·OH hydroxyl radicals through chain reactions. However, due to the slow conversion rate between Fe(Ⅲ) and Fe(Ⅱ), the chain reaction cannot proceed in an orderly manner, resulting in the formation of iron sludge precipitation, which reduces the catalytic efficiency and increases the treatment cost. By introducing nickel ions to form an iron-nickel bimetallic synergistic catalysis, the electron transfer rate between high-valent metals and low-valent metals can be promoted, thereby accelerating the chain reaction and greatly improving the catalytic performance.

[0003] Cyclodextrin (CD) is a general term for a series of truncated cone-shaped cyclic oligosaccharides. It has the characteristics of "internal hydrophobicity and external hydrophilicity" for water molecules. It is produced by amylose under the action of cyclodextrin glucosyltransferase. Generally, it contains 6-12 glucose molecules. Among them, the molecules with 6, 7, and 8 glucose molecules are of great practical significance, which are called α-CD, β-CD, and γ-CD respectively. Due to its own structural characteristics, CD can provide corresponding binding sites like activated enzymes, and act as a main body to encapsulate various objects. The reaction between CD and pollutants or catalytic oxidants mainly includes hydrophobic distribution, hydrogen bonding, and interaction between hydroxyl points on the surface of CD. Since CD itself has both hydrophilic and hydrophobic characteristics, it can form inclusion complexes with many molecules, such as organic molecules, inorganic molecules, etc., by hydrophobic interaction forces and van der Waals forces. It is well known that organic pollutants usually have poor solubility in water, resulting in the inability to fully exert the performance of the catalyst. However, after CD encapsulation, the water solubility of pollutants and catalysts is improved, and the catalyst efficiency is greatly improved.

[0004] β-cyclodextrin (β-CD) has a moderate molecular gap, a wide range of applications and low production costs. It is the most widely used type of cyclodextrin on the market. However, β-CD also has problems with hydrophobic regions and limited catalytic activity, which leads to certain limitations in practical applications. In order to expand the application of cyclodextrin in Fenton-like systems and address the problem of insufficient reusability of existing catalysts, this study proposes a method of using citric acid to modify β-cyclodextrin to form a water-insoluble β-cyclodextrin polymer and an iron-nickel bimetallic catalytic active center to establish a new type of heterogeneous Fenton-like catalyst to catalytically activate H2O2 to degrade PFBA. The present invention has the advantages of being green and environmentally friendly, low price, high efficiency, and can be reused many times. It helps to promote the application of β-cyclodextrin in the field of Fenton-like oxidation and provides a certain theoretical basis for Fenton-like treatment of perfluorinated compound wastewater. Summary of the invention

[0005] The present invention establishes a novel heterogeneous Fenton-like catalyst by modifying β-cyclodextrin with citric acid and then combining it with an iron-nickel bimetallic catalytic active center to catalytically activate H2O2 to degrade PFBA. The optimal system degradation conditions for the degradation of perfluorobutyric acid (PFBA) by using Fe-Ni@CACD material as a Fenton-like catalyst are determined by single-factor experiments. The experimental results show that the material exhibits good degradation efficiency in the Fenton-like system, while overcoming the drawbacks of the traditional Fenton oxidation process, such as the generation of iron mud, difficulty in reagent recovery, and low H2O2 utilization efficiency, showing great potential in treating perfluorinated compound wastewater.

[0006] The specific steps are:

[0007] 1. Preparation of Fenton-like catalyst: 4.00 g of β-cyclodextrin and 2.00 g of anhydrous citric acid (mβ-CD:mCA=2:1) ​​were weighed and added to a 500 mL beaker, and 1.50 g of potassium dihydrogen phosphate and 135 mL of ultrapure water were added to the beaker and mixed evenly. The beaker was placed in a 60 °C water bath with a magnetic stirrer and stirred for 30 min. After stirring for 10 min, 2.942 g of ferrous chloride tetrahydrate and 2.908 g of nickel nitrate hexahydrate (molFe 2 O 4 mol / L) were added. 2+ :molNi 2+ =1.48:1), continue stirring for 20 min until the powder particles in the solution are completely dissolved, seal the beaker with experimental tin foil, transfer the beaker to a 140 ℃ digital display forced air drying oven for reaction for 5 h, and obtain a brown solid product. Take it out and place it outdoors to cool for 30 min, rinse it three times with ultrapure water and anhydrous ethanol to remove surface impurities, and finally dry it in a 60 ℃ vacuum drying oven for 12 h. After grinding, it is the required Fe-Ni@CACD catalyst, which is placed in a desiccator for storage.

[0008] 2. Preparation of PFBA pollutant solution: Take 50.00 μL of 100 mg / L PFBA standard solution into a 50 mL volumetric flask, dilute to the mark with ultrapure water and mix thoroughly by ultrasonication for 5 min to obtain a 0.10 mg / L PFBA solution, and store it at 4°C in the dark.

[0009] 3. In a 100 mL conical flask, accurately add a certain amount of Fe-Ni@CACD Fenton catalyst (0.20, 0.60, 1.00, 1.50, 2.00, 2.50 g / L) and H2O2 (5.00, 10.00, 20.00, 40.00, 60.00, 80.00 mM) obtained in claim 1, and control the total volume of the reaction liquid to be 50 mL. Use hydrochloric acid and sodium hydroxide solution to adjust the initial pH value of the solution (3, 4, 5, 6, 7, 8, 9), wherein the amount of hydrochloric acid and sodium hydroxide solution does not exceed 0.5% of the total volume of the water sample. Then transfer to a digital constant temperature magnetic stirrer for reaction, turn on the stirrer in advance, and adjust the temperature (25, 35, 45, 55 ° C) and the speed (150, 350, 450, 600, 750 r / min). The time of adding H2O2 was taken as the timing zero point. At 30 minutes, 1.00 mL of sample was taken from the reaction solution using a disposable syringe sampler, passed through a 0.22 μm nylon membrane and added to a 2 mL brown injection bottle, followed by adding 0.50 mL of methanol to quench the free radicals. Finally, the concentration of the above samples was detected using an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS).

[0010] The Fe-Ni@CACD catalytic material prepared by the present invention exhibits good degradation efficiency in a Fenton-like system, while overcoming the disadvantages of the traditional Fenton oxidation process, such as the generation of iron sludge, difficulty in reagent recovery, and low H2O2 utilization efficiency, and shows great potential in treating perfluorinated compound wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 These are scanning electron microscope examination images of the product of the present invention (SEM, a: ×150; b: ×5K; c: ×10K; d: 20K; e: EDS).

[0012] Figure 2 This is the specific surface area diagram (BET) of the product of the present invention.

[0013] Figure 3 This is the infrared spectrum (FT-IR) of the product of the present invention.

[0014] Figure 4 This is the X-ray diffraction analysis spectrum (XRD) of the product of the present invention.

[0015] Figure 5 This is the thermogravimetric analysis spectrum (TGA) of the product of the present invention

[0016] Figure 6 A graph showing the change in PFBA degradation performance under different reaction system conditions of the present invention.

[0017] Figure 7 The present invention shows the change of the product's degradation performance against PFBA under different pH conditions.

[0018] Figure 8 A graph showing the change in PFBA degradation performance of the product under different catalyst dosage conditions of the present invention.

[0019] Fig. 9 A graph showing the change in PFBA degradation performance of the product under different H2O2 dosage conditions of the present invention.

[0020] Fig.10 The present invention shows the change in the degradation performance of the product to PFBA under different reaction temperature conditions.

[0021] Fig.11 A graph showing the change in PFBA degradation performance of the product under different reaction speed conditions of the present invention.

[0022] Fig.12 A graph showing the change in PFBA degradation performance of the product under different free radical quenching conditions of the present invention.

[0023] Fig.13 The present invention discloses an electron paramagnetic resonance experiment (EPR) spectrum. DETAILED DESCRIPTION

[0024] Embodiment 1:

[0025] 1. Preparation of Fe-Ni@CACD catalyst:

[0026] Preparation of Fenton-like catalyst: 4.00 g of β-cyclodextrin and 2.00 g of anhydrous citric acid (mβ-CD:mCA=2:1) ​​were weighed and added to a 500 mL beaker, and 1.50 g of potassium dihydrogen phosphate and 135 mL of ultrapure water were added to the beaker and mixed evenly. The beaker was placed in a 60 °C water bath with a magnetic stirrer and stirred for 30 min. After stirring for 10 min, 2.942 g of ferrous chloride tetrahydrate and 2.908 g of nickel nitrate hexahydrate (molFe 2 O 4 ) were added. 2+ :molNi 2+ =1.48:1), continue stirring for 20 min until the powder particles in the solution are completely dissolved, seal the beaker with experimental tin foil, transfer the beaker to a 140 ℃ digital display forced air drying oven for reaction for 5 h, and obtain a brown solid product. Take it out and place it outdoors to cool for 30 min, rinse it three times with ultrapure water and anhydrous ethanol to remove surface impurities, and finally dry it in a 60 ℃ vacuum drying oven for 12 h. After grinding, it is the required Fe-Ni@CACD catalytic material, which is placed in a desiccator for storage.

[0027] The Fe-Ni@CACD materials before and after the reaction were characterized and analyzed by scanning electron microscopy (SEM / EDS), specific surface area analysis (BET), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction analysis (XRD), and thermogravimetric analysis (TGA) to analyze the phase and structure, component composition, and morphology. The contribution of different free radicals in the reaction system to the degradation of perfluorobutyric acid was inferred through free radical quenching experiments, and based on the results of the quenching experiments, the role of free radicals in the Fe-Ni@CACD Fenton-like catalytic system was further analyzed using an electron paramagnetic resonance spectrometer.

[0028] 2. Preparation of PFBA pollutant solution:

[0029] Take 50.00 μL of 100 mg / L PFBA standard solution into a 50 mL volumetric flask, dilute to the mark with ultrapure water and mix thoroughly by ultrasonication for 5 min to obtain a 0.10 mg / L PFBA solution, which is then stored at 4 °C in the dark.

[0030] 3. Effect of different catalyst systems on the performance of Fenton-like degradation of PFBA:

[0031] (1) Add 50.00 mL of 0.10 mg / L PFBA reaction solution into a 100 mL conical flask;

[0032] (2) Adjust the pH to 3 with hydrochloric acid and NaOH solution, where the amount of hydrochloric acid and sodium hydroxide solution does not exceed 0.5% of the total volume of the water sample;

[0033] (3) In a 100 mL conical flask, the initial concentration of PFBA was controlled to be 0.10 mg / L, the dosage of different system catalysts (CACD, Fe@CACD, Fe-Ni@CACD, traditional Fenton reagent FeSO4) was 1.00 g / L, the dosage of H2O2 was 40.00 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at 25 °C and 300 r / min for heating and stirring. The time of adding H2O2 was set as the timing zero, the total reaction time was controlled to be 30 min, and sampling was performed;

[0034] (4) Use a 5 mL disposable syringe sampler to take 1 mL of sample from step (3) and pass it through a 0.22 μm nylon membrane and add it to a 2 mL brown injection bottle, then add 0.50 mL of methanol to quench the free radicals. Finally, an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) was used to determine the concentration of PFBA and obtain the effect of Fenton-like system degradation of PFBA under different reaction systems. The results are as follows: Figure 6 Show.

[0035] 4. Effect of pH value on Fenton-like degradation performance of PFBA:

[0036] (1) Add 50 mL of the prepared 0.10 mg / L PFBA reaction solution into a 100 mL conical flask;

[0037] (2) Use hydrochloric acid and NaOH solution to adjust the pH to 3, 4, 5, 6, 7, 8, and 9 (a total of 7 groups of control experiments), where the amount of hydrochloric acid and sodium hydroxide solution does not exceed 0.5% of the total volume of the water sample;

[0038] (3) In a 100 mL conical flask, the initial concentration of PFBA was controlled to be 0.10 mg / L, the dosage of Fe-Ni@CACD catalytic material was 1.00 g / L, the dosage of H2O2 was 40 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at 25 °C and 300 r / min for heating and stirring. The time of adding H2O2 was used as the timing zero point, the total reaction time was controlled to be 30 min, and sampling was performed;

[0039] (4) Use a 5 mL disposable syringe sampler to take 1 mL of sample from step (3) and pass it through a 0.22 μm nylon membrane. Then add it to a 2 mL brown injection bottle, and then add 0.50 mL of methanol to quench the free radicals. Finally, an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) was used to determine the concentration of PFBA, and the effect of the Fe-Ni@CACD Fenton-like system on the degradation of PFBA under different pH conditions was obtained. The results are shown in the figure. Figure 7 Show.

[0040] 5. Effect of Fe-Ni@CACD catalyst dosage on the degradation performance of PFBA in Fenton-like system:

[0041] (1) Add 50 mL of 0.10 mg / L PFBA reaction solution into a 100 mL conical flask;

[0042] (2) Adjust the pH to 5 with hydrochloric acid and NaOH solution, where the amount of hydrochloric acid and sodium hydroxide solution does not exceed 0.5% of the total volume of the water sample;

[0043] (3) In a 100 mL conical flask, the initial concentration of PFBA was controlled to be 0.10 mg / L, the dosage of Fe-Ni@CACD catalytic material was 0.20 g / L, 0.60 g / L, 1.00 g / L, 1.50 g / L, 2.00 g / L, and 2.50 g / L (a total of 6 control experiments), the dosage of H2O2 was fixed at 40 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at 25 °C and 300 r / min for heating and stirring. The time of adding H2O2 was set as the timing zero, the total reaction time was controlled to be 30 min, and sampling was performed;

[0044] (4) Use a 5 mL disposable syringe sampler to take 1 mL of sample from step (3) and pass it through a 0.22 μm nylon membrane and add it to a 2 mL brown injection bottle, then add 0.50 mL of methanol to quench the free radicals. Finally, an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) was used to determine the concentration of PFBA, and the effect of different Fe-Ni@CACD catalyst dosages on the degradation of PFBA in the Fenton-like system was obtained. The results are shown in the figure. Figure 8 Show.

[0045] 6. Effect of H2O2 dosage on the degradation performance of PFBA in Fenton-like system:

[0046] (1) Add 50 mL of 0.10 mg / L PFBA reaction solution into a 100 mL conical flask;

[0047] (2) Adjust the pH to 5 with hydrochloric acid and NaOH solution, where the amount of hydrochloric acid and sodium hydroxide solution does not exceed 0.5% of the total volume of the water sample;

[0048] (3) In a 100 mL conical flask, the initial concentration of PFBA was controlled to be 0.10 mg / L, the dosage of Fe-Ni@CACD catalytic material was 1.50 g / L, the dosage of H2O2 was 5 mM, 10 mM, 20 mM, 40 mM, 60 mM, and 80 mM (a total of 6 control experiments), and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at 25 °C and 300 r / min for heating and stirring. The time of adding H2O2 was used as the timing zero point, the total reaction time was controlled to be 30 min, and sampling was performed;

[0049] (4) Use a 5 mL disposable syringe sampler to take 1.00 mL of sample from step (3) and pass it through a 0.22 μm nylon membrane and add it to a 2 mL brown injection bottle, then add 0.50 mL of methanol to quench the free radicals. Finally, an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) was used to determine the concentration of PFBA, and the degradation effect of the Fe-Ni@CACD Fenton-like system on PFBA under different H2O2 dosage conditions was obtained, as shown in Figure 2. Fig. 9 Show.

[0050] 7. Effect of reaction temperature on the degradation performance of PFBA in Fenton-like system:

[0051] (1) Add 50 mL of 0.1 mg / L PFBA reaction solution into a 100 mL conical flask;

[0052] (2) Adjust the pH to 5 with hydrochloric acid and NaOH solution, where the amount of hydrochloric acid and sodium hydroxide solution does not exceed 0.5% of the total volume of the water sample;

[0053] (3) In a 100 mL conical flask, the initial concentration of PFBA was controlled to be 0.10 mg / L, the dosage of Fe-Ni@CACD catalytic material was 1.50 g / L, the dosage of H2O2 was fixed at 40 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at 25 ℃, 35 ℃, 45 ℃, and 55 ℃ (a total of 4 control experiments) and a speed of 300 r / min for heating and stirring. The time of adding H2O2 was used as the timing zero point, the total reaction time was controlled to be 30 min, and sampling was performed;

[0054] (4) Use a 5 mL disposable syringe sampler to take 1 mL of sample from step (3) and pass it through a 0.22 μm nylon membrane and add it to a 2 mL brown injection bottle, followed by adding 0.50 mL of methanol to quench the free radicals. Finally, an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) was used to determine the concentration of PFBA, and the degradation effect of the Fe-Ni@CACD Fenton-like system on PFBA under different reaction temperature conditions was obtained, such as Fig.10 .

[0055] 8. Effect of reaction speed on the degradation performance of PBFA in Fenton-like system:

[0056] (1) Add 50 mL of 0.10 mg / L PFBA reaction solution into a 100 mL conical flask;

[0057] (2) Adjust the pH to 5 with hydrochloric acid and NaOH solution, where the amount of hydrochloric acid and sodium hydroxide solution does not exceed 0.5% of the total volume of the water sample;

[0058] (3) In a 100 mL conical flask, the initial concentration of PFBA was controlled to be 0.10 mg / L, the dosage of Fe-Ni@CACD catalytic material was 1.50 g / L, the dosage of H2O2 was fixed at 40 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at a temperature of 35 °C and a speed of 150 r / min, 300 r / min, 450 r / min, 600 r / min, and 750 r / min (a total of 6 groups of control experiments). The H2O2 addition time was used as the timing zero point, and samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min, respectively;

[0059] (4) Use a 5 mL disposable syringe sampler to take 1.00 mL of sample from step (3) and pass it through a 0.22 μm nylon membrane and add it to a 2 mL brown injection bottle, followed by adding 0.50 mL of methanol to quench the free radicals. Finally, an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) was used to determine the concentration of PFBA, and the degradation effect of the Fe-Ni@CACD Fenton-like system under different reaction temperature conditions was obtained, such as Fig.11 Show.

[0060] IX. Contribution of reactive oxygen species to the degradation of PFBA by Fe-Ni@CACD Fenton-like system:

[0061] In order to explore the contribution of active oxygen species in the degradation process of Fe-Ni@CACD Fenton-like system, a quenching experiment with PFBA as the target pollutant was designed. The experimental results are as follows: Fig.12In the quenching experiment, methanol (MeOH) was used as the quencher of ·OH. After adding 10mM methanol, the degradation of PFBA was significantly inhibited. The degradation rate of PFBA was only 17.38% at 30min, while the blank control group without methanol still maintained a degradation rate of 86.72%. This shows that ·OH plays an important role in the degradation process. Fe 3+ Reacting with H2O2 will produce superoxide radicals (·O2 - ), O2 - It can accelerate the cycle of Fe(Ⅲ) / Fe(Ⅱ) and Ni(Ⅱ) / Ni(Ⅰ), thus improving the catalytic efficiency. Add 10mM p-benzoquinone to quench the·O2 - The degradation efficiency of PFBA was reduced after 30 min, and the degradation rate was 63.45%, which was 23.27% less than that of the blank control group. - In the Fe-Ni@CACD Fenton-like system, it played a certain role in the degradation of PFBA, but the overall effect was less than that of ·OH. Finally, in order to explore the role of non-radical oxides in the catalytic degradation process, 10 mM L-histidine was used to quench 1 O2, the quenching results are shown in the figure. After adding L-histidine, there was no obvious inhibitory effect on the degradation of PFBA by Fe-Ni@CACD within 30 minutes, which was almost the same as the blank experimental group. This shows that in the entire Fe-Ni@CACD Fenton-like system, ·OH and ·O2 play the main role. - Therefore, it is preliminarily inferred that the contribution of each ROS in the catalytic process is ·OH>·O2 - > 1 O2.

[0062] According to the quenching experiment results, electron paramagnetic resonance was used to further analyze the ·OH and ·O2 - The role of Fe-Ni@CACD in Fenton-like catalytic system, the experimental results are as follows Fig.13 Show

[0063] The above studies on the Fe-Ni@CACD catalytic material before and after the reaction were carried out by infrared spectroscopy analysis, scanning electron microscopy analysis, X-ray diffraction analysis, X-ray energy spectrum analysis, specific surface area analysis, thermogravimetric analysis, etc. According to the results, the Fe-Ni@CACD catalytic material synthesized by the present invention has great potential to replace the traditional Fenton reagent. As a Fenton-like catalyst, it can efficiently activate H2O2 to produce hydroxyl radicals and superoxide radicals. The hydroxyl radicals and superoxide radicals with strong oxidizing properties attack perfluorobutyric acid, so that it can achieve the purpose of degrading trace perfluorinated compounds in water.

Claims

1. An amorphous Fenton-like catalyst Fe-Ni@CACD, characterized in that: The specific steps of the preparation method are as follows: (1) β-cyclodextrin and anhydrous citric acid are subjected to an esterification reaction under the catalysis of potassium dihydrogen phosphate to prepare a citric acid cross-linked β-cyclodextrin polymer; (2) Add ferrous chloride tetrahydrate and nickel nitrate hexahydrate to a water bath magnetic stirrer and stir for 30 min until the powder particles in the solution are completely dissolved, and seal with tin foil; (3) placing the sealed beaker in step (2) in a digital display air drying oven to dry, thereby obtaining a brown solid product, iron-copper β-cyclodextrin material; (4) The brown solid obtained in step (3) was cooled to room temperature for 30 min, and then rinsed three times with ultrapure water and anhydrous ethanol to remove surface impurities, and dried in a vacuum drying oven. The desired Fe-Ni@CACD catalyst was obtained after grinding, and then placed in a desiccator for storage.

2. The preparation method according to claim 1, characterized in that: In the esterification reaction, β-cyclodextrin and anhydrous citric acid were placed in a 500 mL beaker according to a mass ratio (mβ-CD:mCA=2:1), and 1.50 g of potassium dihydrogen phosphate and 135 mL of ultrapure water were added and mixed evenly.

3. The preparation method according to claim 1, characterized in that: In the Fe-Ni β-cyclodextrin polymerization reaction, the step (1) was placed in a 60°C water bath stirring pot and stirred for 30 min. After stirring for 10 min, a molar ratio of (molFe 2+ :molNi 2+ =1.48:1) of ferrous chloride tetrahydrate and nickel nitrate hexahydrate, and continue stirring for 20 min.

4. The preparation method according to claim 1, characterized in that: The temperature of the digital display forced air drying oven in step (3) is 140°C, and the reaction time is 5 h.

5. The preparation method according to claim 1, characterized in that: In step (4), the temperature of the vacuum drying oven is 60°C and the drying time is 12 hours.

6. An amorphous Fenton-like catalyst Fe-Ni@CACD, characterized in that: The catalyst Fe-Ni@CACD is prepared by the preparation method according to any one of claims 1 to 5.

7. The catalyst Fe-Ni@CACD as claimed in claim 6 can be applied to activate H2O2 advanced oxidation technology, characterized in that: As a Fenton-like catalyst, Fe-Ni@CACD can efficiently catalyze and activate H2O2 to produce hydroxyl radicals and superoxide radicals, which attack CF in perfluorinated compounds (perfluorobutyric acid), thereby achieving the purpose of degrading perfluorinated compounds in water.